Developing complaint and feedback management system (sistem pengurusan aduan dan maklumbalas) / Nur Shaliza Sapiai... [et al.] - Sapiai, Nur Shaliza; Arifin, Noorfadzilah; Abdul Rahman, Firdaus; Che Yusoff Gemeti, Mazlam; Ismail, Mohd Nasir; Abdul Rahman, Sapiai (2010)
The modem rapid advancements in computers, networking, communication and mobility created and increased information access and retrieval. Computers become portable and cheap enough to accommodate and manage high volume of data. The system presented in this paper known as Sistem Pengurusan Aduan dan Maklum balas or (SPAM) is an electronic complaint and feedback initiative to manage the collection of complaints in Universiti Teknologi MARA Kelantan Kampus Kota Bharu (UiTM KKB). SPAM was established at 2009 in October to be a central repository for managing any complaint received by UiTM KKB. SPAM provides easy access and retrieval through intranet and internet. This paper elaborates step by step on the process of developing SPAM and how the system work to achieve and fullfill the management needs. At the end of the discussion, this paper reveal the outputs that produced by SPAM.